2021
DOI: 10.1109/tns.2021.3069110
|View full text |Cite
|
Sign up to set email alerts
|

Investigations Into X-Band Dielectric Assist Accelerating Structures for Future Linear Accelerators

Abstract: Dielectric assist accelerating (DAA) structures are being studied as an alternative to conventional disk-loaded copper structures. This paper investigates numerically an efficient Xband DAA structure operating in a higher order mode of TM02-π. This accelerating structure consists of dielectric disks with irises arranged periodically in a metallic enclosure. Through optimizations, the RF power loss on the metallic wall can be significantly reduced, resulting in an extremely high quality factor = and a very high… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…( 5) and Boris method agree perfectly with each other, a fact that allows us to justify and validate the simplification made in the third equation of the system (2) of disregarding the term proportional to the magnetic field H 0 . The analytical approximation (6) gives reasonable values for the electron trajectory, although the fact that its validity is restricted to very small times means that as time goes by the approximate trajectory differs from the full equation (5). In Fig.…”
Section: A Down Zonementioning
confidence: 92%
See 1 more Smart Citation
“…( 5) and Boris method agree perfectly with each other, a fact that allows us to justify and validate the simplification made in the third equation of the system (2) of disregarding the term proportional to the magnetic field H 0 . The analytical approximation (6) gives reasonable values for the electron trajectory, although the fact that its validity is restricted to very small times means that as time goes by the approximate trajectory differs from the full equation (5). In Fig.…”
Section: A Down Zonementioning
confidence: 92%
“…The advantage of the DAA structure is that it has an extremely high quality factor and a very high shunt impedance at room temperature since the electromagnetic field distribution of the accelerating mode T M 02 reduces greatly the losses on the metallic wall as compared to that of a T M 01 mode of the pillbox cylindrical cavity. Several DAA designs have been presented in the literature, and even some prototypes have been build and tested [4], [5], [6]. Although their good performance in terms of quality factor and shunt impedance has been demonstrated with measurements, it has also been found that DAA structures suffer multipactor during operation.…”
Section: Introductionmentioning
confidence: 99%
“…The DAA structures [39,42] consist of axially symmetric dielectric cylinders with irises periodically arranged in a metallic enclosure operating in standing wave π-mode, as illustrated in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Based on these technologies, a Dielectric Assist Accelerating (DAA) structure proposed by Satoh et al [39][40][41] at C-band frequency is of particular interest since it achieved extremely high quality factor and shunt impedance. Later, this design was studied at X-band as a proposal for future linear accelerators [42] due to its high field holding capability. Building on these developments, a DAA structure for low beta particles operating at low frequency (S-band) is studied for the first time in this work, as a solution for compact linear accelerators of low energy and low beam current, such as medical accelerators for Hadrontherapy treatments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation